Investigating climate change and emerging theoretical perspectives: a systematic theoretical review and thematic analysis - James Mubangizi; Joseph M. Ntayi; Muyiwa Samuel Adaramola; Muyiwa Samuel Adaramola; Faisal Buyinza; Ronnette Atukunda; Simon Echegu (Frontiers in Environmental Economics)
This study aims to review existing studies on climate change theories, as well as other theories from other disciplines, including economics, political science, sociology, management, cultural studies, and psychology that have been used to explain climate change. Furthermore, it seeks to identify emerging theoretical perspectives in climate change research. This study analyzed and reviewed 73 articles and reports on climate change theories and emerging theoretical perspectives using systematic theoretical review and thematic analysis methodologies. Data sources included Science Direct, Taylor & Francis, Emerald, Google Scholar, and Google general. The findings indicate the multidimensional nature of climate change theories, encompassing four primary climate change theories, interdisciplinary theories, and emerging theoretical perspectives. This variation suggests that no single theory can fully explain the complexity of climate change, necessitating an integrated approach. The review revealed that anthropogenic climate change theory dominates the literature, representing 37.5% (12 papers) of the reviewed literature, reinforcing the strong scientific consensus among academics, environmentalists, and policymakers that human-induced greenhouse gas emissions are the primary drivers of climate change. The paper concludes by identifying four critical knowledge gaps. In addition, the findings will be useful for policymakers, industry stakeholders, and educators in developing effective mitigation and adaptation strategies.